Real wage chronologies - Louis N. Christofides; Amy Chen Peng (Center for Economic Studies and ifo Institute (CESifo), 2007)
We process information in a large number of wage contracts, signed over a period of several decades, to generate the long-run history of the real wage for each bargaining pair. We term these hitherto unexamined histories chronologies'. We are able to generate 1574 continuous real wage chronologies and we examine the evolution of the real wage in each case. We explore the influence of productivity growth, the industrial relations record of the pair, the influence of industry and region as well as the initial wage on the growth of the real wage rate over the decades in the sample. We conclude that these economically important forces can be statistically discerned in the wage chronologies.
Keywords: E31; J41; J50; 330; Reallohn; Regionale Entwicklung; Branchenentwicklung; Produktivität; Kanada